Figure 24 from: Eberhardt U, Beker HJ, Borgen T, Knudsen H, Schütz N, Elborne SA (2021) A survey of Hebeloma (Hymenogastraceae) in Greenland. MycoKeys 79: 17-118. https://doi.org/10.3897/mycokeys.79.63363 - Eberhardt, Ursula; Beker, Henry J.; Borgen, Torbjørn; Knudsen, Henning; Schütz, Nicole; Elborne, Steen A. (Zenodo, 2021)
Figure 24 Hebeloma aurantioumbrinumA SAE-2016.146, photograph S.A. Elborne B distribution of cited collections C spores ×1600 and D cheilocystidia ×1000 of SAE-2016.146 in Melzer's reagent. Scale bars: 5 µm; microphotographs H.K.J. Beker.